DRUG-DRUG INTERACTIONS IN PSYCHIATRIC PATIENTS: IDENTIFYING HIGH-RISK COMBINATIONS AND MITIGATION STRATEGIES - SHAMSHAD, H; SHAMSHAD, S (Biological and Clinical Sciences Research Journal, 2022)
Psychiatric patients are at a high risk of severe adverse drug events (ADEs) due to potential drug-drug interactions (DDIs). These interactions can worsen existing health conditions and complicate treatment outcomes. Objective: This study aimed to identify and evaluate the drug-drug interactions (DDIs) of psychoactive drugs among mental health patients and propose effective prevention measures. A retrospective study was conducted at the Department of Pharmacy, Lady Reading Hospital, Peshawar, from January 1, 2021, to July 31, 2021. The study included all psychiatric patients treated during this period. Medication records were re-examined to identify drug-drug interactions (DDIs) using reliable drug interaction databases. Adverse effects resulting from these interactions were documented. Statistical analysis assessed the frequency and severity of the identified DDIs. Mitigation strategies were developed based on the probability and clinical relevance of the interactions. These strategies included drug adjustments, regular monitoring of patients, and patient education aimed at reducing the risk of adverse effects. The major DDIs frequently occur with commonly used psychiatric medications such as antipsychotics, antidepressants, and mood stabilisers. Common adverse effects included sedation, cardiovascular complications, and increased risk of serotonin syndrome. Mitigation measures, such as drug adjustment, regular monitoring, and patient education, were suggested to reduce the risk of adverse effects. Psychiatric patients are predisposed to severe ADEs due to DDIs, which are often difficult to predict. Mitigation measures such as appropriate drug adjustments and patient education are essential to enhance patient safety and treatment outcomes.